Adaptive Ku-Band Solar Rectenna for Internet-of-Things- (IoT)-over-Satellite Applications. (17th July 2021) - Baccouch, Chokri; Bahhar, Chayma; Sakli, Hedi; Aguili, Taoufik
Abstract : The emergence of new IoT applications in regional and remote areas has increased the need for a global IoT connectivity beyond existing terrestrial network coverage. However, in many cases, it is not economically viable to build a dedicated terrestrial network to cover these remote areas due to population sparsity and the lack of business case. In this paper, we propose a framework for designing a solar rectenna for IoT-over-satellite applications using nanosatellites. Utilizing such a framework will allow valuable radio spectrum resources to be shared between satellite and terrestrial users. Thus, the autonomous power supply of these objects becomes a big challenge. Indeed, the harvest of solar energy and the conversion of RF energy into electric voltage are a hot topic. Our contribution consists in offering a solar rectenna system to collect solar and RF energy as well as the radio frequency transmission. A parametric study is carried out to follow the influence on the performance of this system. A topology of rectifying circuits is proposed in the present work. The parametric study has shown that the efficiency RF/DC conversion can reach 23.2% for an input power of 5 dBm and a load resistance of 2 kΩ . To ensure the satellite communication of IoT-connected autonomous objects, this system is operated in the X or Ku band.